Mead - de Oliveira, Mariana Dâmaris [UNESP]; de Sá, Igor Silva [UNESP]; de Souza, João Victor Martinelli [UNESP]; de Castilhos, Maurício Bonatto Machado; Del Bianchi, Vanildo Luiz [UNESP] (My University, 2021)
Mead is a fermented product from honey bees. This alcoholic beverage is recognized as one of the oldest consumed by man and archaeological evidence of its production dates back to 7000 BC. It is popularly produced at home and/or in small factories. The raw material has great influence on the quality and characteristics found in the final product, and different types of mead can be distinguished based on the kind of honey and the producer bees, honey/water ratio, addition of spices and/or fruits, yeast utilized, method of the must preparation, maturation and aging. Mead production has increased remarkably in recent years, and more and more attention has been paid to improving its production parameters and quality.
Keywords: Chemical; Mead; Raw material; Sensory; Technology